The Response of Radiative Forcing to High Spatiotemporally Resolved Land‐Use Change and Transition From 1982 to 2010 in China - Xiaohu Jian; Xiaodong Zhang; Yijie Liu; Xinrui Liu; Kaijie Chen; Linfei Wang; Jixiang Li; Yuan Zhao; Jinmu Luo; Ruiyu Zhugu; Jianmin Ma (Geophysical Research Letters)
Abstract Significant uncertainties remain in the estimate of radiative forcing (RF) induced by land‐use change (LUC), partially attributable to the lack of reliable LUC data with a high spatiotemporal resolution. We implemented a high spatiotemporally resolved LUC data set in an earth system model (OSCAR) to examine the response of RF to LUC from 1982 to 2010 in China. Results were compared with the RF estimated using a low spatiotemporally resolved LUC inventory employed previously. The updated LUC data set reduces negative RF by −3.8% from 2000 to 2010 due to the changes in surface albedo subject to LU transition. The simulated mean RF driven by CO2 associated with LUC from 1982 to 2010 using a high spatiotemporally resolved LUC data set reached 0.074 W m−2, considerably higher than 0.022 W m−2 of mean RF derived from the low spatiotemporally resolved LUC inventory, implying increasing net RF and more substantial LUC induced warming.